Approaches between history and the humanities - Mohammed, Ali Jassim (Journal of Tikrit University for Humanities, 2022)
History is closely linked to social and human sciences. Although the humanities overlap with each other in their subjects, circumstances and results at times, and despite the independence of human disciplines, but that independence is intended for academic organization, and does not eliminate the need for each discipline for the other. The integration of history with other sciences is intended to achieve the highest goal of specialization, namely, to show facts, to know the past conditions, and to identify the previous variables. Consequently, historical studies have therefore opened up broad horizons for leaders, kings, presidents and the general public to avoid the mistakes of the oldest, and then to make sense of it to move forward towards a better present and future, and thereby fulfilling the service of society. Thus, the science of society, and geography, economics, politics, sociology and languages are at the forefront of the human sciences that are at the heart of the science of history on the one hand, or enter with it as auxiliary sciences on the other.